1996
DOI: 10.1093/ajcn/63.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Red wine consumption does not affect oxidizability of low-density lipoproteins in volunteers

Abstract: Please be advised that this information was generated on 2018-05-11 and may be subject to change. ABSTRACTPhenolic compounds in red wine may protect low-density lipoprotein,s (LDL) against oxidative modification, thereby reducing the risk of cardiovascular morbidity. However, in vivo data are scarce. We gave 13 healthy volunteers 550 mL red wine and another 11 volunteers white wine for 4 wk in a random ized double-blind trial. Interference by alcoholic components of wine was eliminated by reducing the alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(80 citation statements)
references
References 35 publications
(29 reference statements)
2
78
0
Order By: Relevance
“…Nevertheless, our results agree with those of Sharpe et al (1995). It is also worth noting that De Rijke et al (1996) reported no difference in LDL protecting effects of red wine as compared with white wine in the particular case of lower alcohol content (3.5%). In this respect, although we have no precise information about proanthocyanidins and anthocyanins of red wine used by these authors, it seems that the daily ingested amounts of`catechins' and¯avonols were similar to those of the present paper and, interestingly, that the amounts present in white wine were extremely low.…”
Section: Discussionmentioning
confidence: 87%
“…Nevertheless, our results agree with those of Sharpe et al (1995). It is also worth noting that De Rijke et al (1996) reported no difference in LDL protecting effects of red wine as compared with white wine in the particular case of lower alcohol content (3.5%). In this respect, although we have no precise information about proanthocyanidins and anthocyanins of red wine used by these authors, it seems that the daily ingested amounts of`catechins' and¯avonols were similar to those of the present paper and, interestingly, that the amounts present in white wine were extremely low.…”
Section: Discussionmentioning
confidence: 87%
“…However, other similar studies reported no such effects (25,33) . It is interesting that in one of these studies (47) , the authors explained that the storage conditions of the tested product had not been the same as in a previous one where they had observed a decrease in LDL oxidation.…”
Section: Effects On Ldl Oxidationmentioning
confidence: 79%
“…Also, grape polyphenols may have a reducing effect in cardiac fibrosis, a process occurring in cases of hypertension (17) Thirty-five healthy women 4 weeks Red wine with 13·5 % ethanol and 1·9 g total polyphenols/l or white wine with 13 % ethanol and 0·31 g total polyphenols/l Agewall et al (2000) (18) Twelve healthy subjects Acute intake Red wine with 1·9 g total polyphenols/l and 12·5 % ethanol or dealcoholised red wine with 1·1 g total polyphenols/l (250 ml in all groups) Cross-over design Naissides et al (2004) (19) Seventeen postmenopausal women Acute intake Dealcoholised red wine with 2·2 g total polyphenols/l, white wine with 2·2 g total polyphenols/l or water Cross-over design Williams et al (2004) (20) Fourteen men with stable IHD Acute intake Red wine with 13·5 % ethanol and 1·2 g total polyphenols/l, white wine with 13 % ethanol and 0·2 g total polyphenols/l or non-alcoholic drink without polyphenols Cross-over design Pignatelli et al (2006) (21) Twenty healthy subjects 3 weeks Red wine with 12·5 % ethanol and 1·2 g total polyphenols/l or white wine with 12·5 % ethanol and 0·18 g total polyphenols/l Castilla et al (2008) (24) Thirty-two haemodialysed patients 2 weeks Red grape concentrate (100 ml/d ¼ 600 mg total polyphenols/d), 800 IU (20 mg) vitamin E/d or both De Rijke et al (1996) (25) Twenty-four healthy subjects 2 weeks, then 4 weeks with different treatments (33) Nine hypercholesterolaemic and eight normocholesterolaemic subjects (45) Hypertensive men 8 weeks Grape juice with 2·1 g total polyphenols/l or placebo (11 ml/kg weight per d in all groups) Ward et al (2005) (46) Hypertensive subjects 6 weeks Vitamin C, polyphenols from red grape seeds (1 g/d), both or control Chou et al (2001) (47) Fifteen healthy subjects 1 week Extract from grape peel with 5 % total polyphenols (600 mg extract/d) Matsuo et al (2001) (51) Six men Acute intake Red wine, ethanol, polyphenols from red wine Cross-over design Freedman et al (2001) (52) Twenty healthy volunteers 2 weeks Purple grape juice (7 ml/kg weight per d) Boban et al (2006) (53) Nine men Acute intake Red wine, dealcoholised red wine, polyphenols from red wine, ethanol -water solution, water Cross-over design Whelan et al (2004) (10...…”
Section: Effects On Blood Pressure: Endothelial Functionmentioning
confidence: 99%
“…Nevertheless, only in one study diet was fully controlled (Kondo et al, 1994), some included smokers Sharpe et al, 1995;Suzukawa et al, 1994) or lacked information on smoking habits (Gorrinstein et al, 1997;Kondo et al, 1994;Maxwell et al, 1994;Whitehead et al, 1995). Most studies were restricted to wine consumption De Rijke et al, 1996;Fuhrman et al, 1995;Maxwell et al, 1994;Sharpe et al, 1995;Whitehead et al, 1995), some included spirits (Kondo et al, 1994;Nigdikar et al, 1998;Suzukawa et al, 1994) and two only focussed on beer consumption Gorrinstein et al, 1997). Three studies evaluated the acute antioxidant effects of wine consumption on antioxidant status Maxwell et al, 1994;Whitehead et al, 1995) which may have limited relevance in terms of chronic disease prevention.…”
Section: Introductionmentioning
confidence: 99%